Effect of Methamphetamine on Spectral Binding, Ligand Docking and Metabolism of Anti-HIV Drugs with CYP3A4. - Anantha R Nookala (PLoS ONE, 2016)
Cytochrome P450 3A4 (CYP3A4) is the major drug metabolic enzyme, and is involved in the metabolism of antiretroviral drugs, especially protease inhibitors (PIs). This study was undertaken to examine the effect of methamphetamine on the binding and metabolism of PIs with CYP3A4. We showed that methamphetamine exhibits a type I spectral change upon binding to CYP3A4 with δAmax and KD of 0.016±0.001 and 204±18 μM, respectively. Methamphetamine-CYP3A4 docking showed that methamphetamine binds to the heme of CYP3A4 in two modes, both leading to N-demethylation. We then studied the effect of methamphetamine binding on PIs with CYP3A4. Our results showed that methamphetamine alters spectral binding of nelfinavir but not the other type I PIs (lopinavir, atazanavir, tipranavir). The change in spectral binding for nelfinavir was observed at both δAmax (0.004±0.0003 vs. 0.0068±0.0001) and KD (1.42±0.36 vs.2.93±0.08 μM) levels. We further tested effect of methamphetamine on binding of 2 type II PIs; ritonavir and indinavir. Our results showed that methamphetamine alters the ritonavir binding to CYP3A4 by decreasing both the δAmax (0.0038±0.0003 vs. 0.0055±0.0003) and KD (0.043±0.0001 vs. 0.065±0.001 nM), while indinavir showed only reduced KD in presence of methamphetamine (0.086±0.01 vs. 0.174±0.03 nM). Furthermore, LC-MS/MS studies in high CYP3A4 human liver microsomes showed a decrease in the formation of hydroxy ritonavir in the presence of methamphetamine. Finally, CYP3A4 docking with lopinavir and ritonavir in the absence and presence of methamphetamine showed that methamphetamine alters the docking of ritonavir, which is consistent with the results obtained from spectral binding and metabolism studies. Overall, our results demonstrated differential effects of methamphetamine on the binding and metabolism of PIs with CYP3A4. These findings have clinical implication in terms of drug dose adjustment of antiretroviral medication, especially with ritonavir-boosted antiretroviral therapy, in HIV-1-infected individuals who abuse methamphetamine.